Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
giải
\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)
\(\left(x+x+x+x\right)+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)
\(4x=\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)
Đặt A = \(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\)
vậy ta có : \(4x+\frac{15}{16}=1\)
suy ra : \(4x=1-\frac{15}{16}\)
\(4x=\frac{1}{16}\)
\(x=\frac{1}{16}:4=\frac{1}{16}x\frac{1}{4}=\frac{1}{64}\)
Vậy \(x=\frac{1}{64}\)
\(\left(\frac{7}{2}+2x\right).\frac{8}{3}=\frac{16}{3}\)
\(\frac{7}{2}+2x=\frac{16}{3}:\frac{8}{3}\)
\(\frac{7}{2}+2x=2\)
\(2x=2-\frac{7}{2}\)
\(2x=\frac{-3}{2}\)
\(x=\frac{-3}{2}:2\)
\(x=\frac{-3}{4}\)
\(\frac{1}{3}.x+0,5x=0,75\)
\(\frac{1}{3}x+\frac{1}{2}x=\frac{3}{4}\)
\(x.\left(\frac{1}{3}+\frac{1}{2}\right)=\frac{3}{4}\)
\(x.\frac{5}{6}=\frac{3}{4}\)
\(x=\frac{3}{4}:\frac{5}{6}\)
\(x=\frac{9}{10}\)
\(1\frac{1}{7}\cdot1\frac{1}{8}\cdot1\frac{1}{9}\cdot...\cdot1\frac{1}{50}\)
\(=\frac{8}{7}\cdot\frac{9}{8}\cdot\frac{10}{9}\cdot...\cdot\frac{51}{50}\)
\(=\frac{8\cdot9\cdot10\cdot...\cdot51}{7\cdot8\cdot9\cdot...\cdot50}\)
\(=\frac{51}{7}\)
\(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}+\frac{1}{32}+\frac{1}{64}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{8}+\frac{1}{8}-\frac{1}{16}+\frac{1}{16}-\frac{1}{32}+\frac{1}{32}-\frac{1}{64}\)
\(=1-\frac{1}{64}\)
\(=\frac{63}{64}\)
\(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}+\frac{1}{32}+\frac{1}{64}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{8}+\frac{1}{8}-\frac{1}{16}+\frac{1}{16}-\frac{1}{32}+\frac{1}{32}-\frac{1}{64}+\frac{1}{64}\)
\(=1-\frac{1}{64}\)
\(=\frac{63}{64}\)
B=1x3/2x2x2x4/3x3x3x5/4x4x...x10x12/11x11
B=1x3x2x4x3x5x...x10x12/2x2x3x3x4x4x...x11x11
B=(1x2x3x...x10)x(2x3x5x...x12)/(2x3x4x...x11)x(2x3x4x...x11)
B=1x12/11x2
B=12/22
B=6/11
Vậy B = 6/11
(\(x+\dfrac{1}{2}\)) + (\(x+\dfrac{1}{4}\)) + (\(x+\dfrac{1}{8}\)) + (\(x+\dfrac{1}{16}\)) = \(\dfrac{31}{16}\)
\(x+\dfrac{1}{2}+x+\dfrac{1}{4}\) + \(x+\dfrac{1}{8}\) + \(x\) + \(\dfrac{1}{16}\) = \(\dfrac{31}{16}\)
(\(x+x+x+x\)) + (\(\dfrac{1}{2}\) + \(\dfrac{1}{4}\) + \(\dfrac{1}{8}\) + \(\dfrac{1}{16}\)) = \(\dfrac{31}{16}\)
4\(x\) + (\(\dfrac{8}{16}\) + \(\dfrac{4}{16}\) + \(\dfrac{2}{16}\) + \(\dfrac{1}{16}\)) = \(\dfrac{31}{16}\)
4\(x\) + \(\dfrac{15}{16}\) = \(\dfrac{31}{16}\)
4\(x\) = \(\dfrac{31}{16}\) - \(\dfrac{15}{16}\)
4\(x\) = 1
\(x=\dfrac{1}{4}\)
(x + 1/2) + (x + 1/4) + (x + 1/8) + (x + 1/16) = 31/16
x \(\times\) 4 + (1/2 + 1/4 + 1/8 + 1/16) = 31/16
Đặt 1/2 + 1/4 + 1/8 + 1/16 là A
A = 1/2 + 1/4 + 1/8 + 1/16
2xA = 1 + 1/2 + 1/4 + 1/8
2xA-A = (1 + 1/2 + 1/4 + 1/8)-(1/2 + 1/4 + 1/8 + 1/16)
A = 1 - 1/16
A = 15/16
Thay ...
x \(\times\) 4 + 15/16 = 31/16
x \(\times\) 4 = 1
x = 0,25
Vậy x = 0,25